'Run with the fox and hunt with the hounds': Managerial Trade-Unionism and the British Association of Colliery Management, 1947–1994. Issue 39 (September 2018) - Perchard, Andrew; Gildart, Keith
Abstract : This article examines the evolution of managerial trade-unionism in the British coal industry, focusing on the development of the British Association of Colliery Management (BACM) from 1947 until 1994. It explores the organization's identity from its formation as a conservative staff association to its emergence as a distinct trade union, analysing its policy towards industrial action and strike cover, affiliation to the Trades Union Congress (TUC), colliery closures, and the privatization of the coal industry. It examines BACM's relationship with the National Union of Mineworkers (NUM) and the National Association of Colliery Overmen, Deputies and Shotfirers (NACODS), the National Coal Board (NCB) and subsequently the British Coal Corporation (BCC). This is considered within the wider context of managerial identity in the coal industry and discussions over the growth of managerial (and white-collar) trade unions in post-war Britain.